Future Network Systems and Security Second International Conference, FNSS 2016, Paris, France, November 23-25, 2016, Proceedings - Doss, Robin; Piramuthu, Selwyn; Zhou, Wei (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the Second International Conference on Future Network Systems and Security, FNSS 2016, held in Paris, France, in November 2016. The 12 full papers and one short paper presented were carefully reviewed and selected from 34 submissions. The papers focus on the technology, communications, systems and security aspects of relevance to the network of the future.